2021
DOI: 10.1007/s43615-021-00083-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Methodological Framework for the Evaluation of the Material and Energy Recovery Potential of Municipal Solid Waste Management: Implementation in Five Greek Regions

Abstract: Problem According to the Landfill Directive, the proportion of municipal waste disposed of in landfills should be reduced to 10% w/w or less of the total amount of municipal waste generated by 2035. It should be highlighted that even though the regional waste management plans in Greece took into consideration the recycling targets set by the European Union, the proportion of municipal waste disposed of by landfilling was about 80% w/w in 2020.Purpose The present study aims to introduce a methodological framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In transposition of the Directive, several countries are implementing national waste-management plans and measures to reduce food waste. For instance, Bulgaria introduced the National Waste Management Plan 2021–2028 [ 28 ], the Greek Ministry of Environment set a strategic goal for the period 2021–2030 [ 29 ], Hungary aims to reduce food waste and losses through the National Waste Management Plan 2021–2027 [ 30 ], and Romania ordered the “Government Decision 92/2021” on its waste regime [ 31 ]. Incentives such as tax deductions for companies that save food by donation are also present in some EU countries [ 32 ]; this is an effective food-waste reduction policy that was introduced several years ago.…”
Section: Mitigation Of Food Waste Without Compromising Food Safetymentioning
confidence: 99%
“…In transposition of the Directive, several countries are implementing national waste-management plans and measures to reduce food waste. For instance, Bulgaria introduced the National Waste Management Plan 2021–2028 [ 28 ], the Greek Ministry of Environment set a strategic goal for the period 2021–2030 [ 29 ], Hungary aims to reduce food waste and losses through the National Waste Management Plan 2021–2027 [ 30 ], and Romania ordered the “Government Decision 92/2021” on its waste regime [ 31 ]. Incentives such as tax deductions for companies that save food by donation are also present in some EU countries [ 32 ]; this is an effective food-waste reduction policy that was introduced several years ago.…”
Section: Mitigation Of Food Waste Without Compromising Food Safetymentioning
confidence: 99%
“…However, the role of nuclear power in reducing GHG emissions also faces significant uncertainties [15,16] not to mention those regarding the disposal of nuclear waste and the catastrophic consequences of nuclear accidents [16]. The fossil fuel power stations coupled with a flue gas carbon capture and storage (CCS) system are also a special case [12,17,18].…”
Section: Genesis and Ensuing Backgroundmentioning
confidence: 99%
“…Miller and Ip [26] suggested that materials such as bamboo and short-term crops can be considered having negative embodied carbon. There is a growing focus on the embodied carbon of materials and materials CE [12,18,23,33,39]. This approach contributes directly or indirectly to the prevailing green buildings design practice, i.e., Leadership in Energy and Environmental Design (LEED), a rating system designed to lower the negative environmental impact of a built environment [40].…”
Section: The Role Of Government Industry and Ngos In Low-carbon Agementioning
confidence: 99%
See 1 more Smart Citation